1993
DOI: 10.1111/j.1751-1097.1993.tb02332.x
|View full text |Cite
|
Sign up to set email alerts
|

ABSORPTION SPECTRA OF LEAVES CORRECTED FOR SCATTERING and DISTRIBUTIONAL ERROR: A RADIATIVE TRANSFER and ABSORPTION STATISTICS TREATMENT

Abstract: A comprehensive treatment of light propagation through intact leaves based on the theories of radiative transfer and absorption statistics was used to calculate the theoretical absorption spectra of the chlorophyll-containing particles under conditions of multiple scattering and pigment spatial distribution equivalent to those in a leaf. These spectra were compared with the experimental in vivo spectra of leaves and in vitro spectra of chlorophyll-protein complexes extracted form these leaves. We conclude that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 23 publications
1
48
1
Order By: Relevance
“…The differences observed between species may be related to differences in the distribution of chlorophyll in tree leaves as a result of the structural organization of chlorophyll molecules in chloroplasts, chloroplasts in cells, and cells in leaves (Fukshansky et al, 1993). It is generally accepted that with increasing heterogeneity of chlorophyll distribution inside a leaf, the absorption of a given amount of chlorophyll decreases (Uddling et al, 2007) and the relationship between SPAD and chlorophyll content deviates more from linearity.…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed between species may be related to differences in the distribution of chlorophyll in tree leaves as a result of the structural organization of chlorophyll molecules in chloroplasts, chloroplasts in cells, and cells in leaves (Fukshansky et al, 1993). It is generally accepted that with increasing heterogeneity of chlorophyll distribution inside a leaf, the absorption of a given amount of chlorophyll decreases (Uddling et al, 2007) and the relationship between SPAD and chlorophyll content deviates more from linearity.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is clear that the relationship between Chl content and Chl meter-reading does not exhibit a similar pattern for all species. These differences among species may be related to the non-uniform distribution of Chl in leaves as an effect of the clustered structural organization of Chl molecules in chloroplasts, chloroplasts in cells, and cells in leaves (Fukshansky et al 1993). The curvilinear relationship suggested that CCM-200 underestimated total Chl at high concentrations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The new measuring system opens the way to a profound assessment of the specific contributions of various leaf regions to the overall photosynthetic activity. This may be considered an important step forward towards an integrative modelling of leaf photosynthesis, the theoretical basis for which has been advanced by Fukshansky and co-workers Fukshansky et al 1992;Martinez v. Remisowsky et al 1992). Fiberoptic microprobe measurements can provide information on the vertical gradient of photosynthetic activity within a leaf, while fluorescence image analysis provides information on the lateral distribution, as viewed from the surface (Myers et al 1994;Siebke and Weis 1995;Genty and Meyer 1995).…”
Section: Discussionmentioning
confidence: 99%